Inventário urbano de Tupanciretã/RS: um olhar sobre o patrimônio arquitetônico e cultural da terra da mãe de deus - Oliveira, Tarcísio Dorn de (2011)
The architecture and the various places in the city are the scene of our memories and are located in that built landscapes allude to symbolic meanings, which evoke narratives related to our lives. So the way we interpret our experiences in space becomes our reality and enables us to give meaning to our physical world. A key aspect in the life of a city, so is the set of her memories that emerge: the urban memory is the reality that marks our own transience in history, while announcing the possibility of transcending our individual temporality. This paper deals with an issue of extreme importance to the city of Tupanciretã: the rescue of urban memory through inventory, to articulate the preservation of the demands of social and economic development of the municipality, with an emphasis on analysis, focusing on the historical, socio-cultural and architectural each building with the intention to participate in policy and urban development plans, with regard to areas to be preserved and others subject to the urban renewal plan in coordination director.